2015
DOI: 10.1103/physrevb.91.144424
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic phase diagram of an Fe monolayer on W(110) and Ta(110) surfaces based onab initiocalculations

Abstract: We present detailed investigations of the magnetic properties of an Fe monolayer on W and Ta (110) surfaces based on the ab initio screened Korringa-Kohn-Rostoker method. By calculating tensorial exchange coupling coefficients, the ground states of the systems are determined using atomistic spin dynamics simulations. Different types of ground states are found in the systems as a function of relaxation of the Fe layer. In the case of the W(110) substrate this is reflected in a reorientation of the easy axis fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Moreover, it is known that the exchange coupling of Fe could be both ferromagnetic and antiferromagnetic which depends on the substrates' d-band filling. [42][43][44] Recently, ab initio calculation showed that ferromagnetic NN and AFM NNN interaction could coexist in multilayer Pt 1−x Ir x / Fe/Pd structures, 45 where our simulation results are promising and remain to be verified experimentally.…”
Section: B Hysteresis Loopmentioning
confidence: 72%
“…Moreover, it is known that the exchange coupling of Fe could be both ferromagnetic and antiferromagnetic which depends on the substrates' d-band filling. [42][43][44] Recently, ab initio calculation showed that ferromagnetic NN and AFM NNN interaction could coexist in multilayer Pt 1−x Ir x / Fe/Pd structures, 45 where our simulation results are promising and remain to be verified experimentally.…”
Section: B Hysteresis Loopmentioning
confidence: 72%
“…Besides the Dzyaloshinsky-Moriya interaction, the presence of frustrated isotropic exchange interactions has also been demonstrated recently in several ultrathin film systems [40][41][42]. In particular, skyrmions have been observed in numerical simulations performed for a (Pt 1−x Ir x )/Fe bilayer on Pd(111) in Ref.…”
Section: Introductionmentioning
confidence: 89%
“…We notice an inward relaxation for the Fe overlayer on W(110) for the bridge site by À12.68%, in agreement with the experiment 35 and theoretical results. 1,11,29 We have also computed the binding energies and found the value of 5.10 eV for Fe ML on the bridge site, which is about 0.94 eV larger than that on the top site. The diagonal bridge 36 The inward relaxation explains well the stronger binding of the Fe on the bridge site as shown in Table 3.…”
Section: Adsorption Of 1-ml Fe On W(110)mentioning
confidence: 94%
“…However, other authors [8][9][10] have indicated a FM ground state in this system by using micromagnetic and atomistic ab initio calculations. More recently, Rózsa et al 11 reported on the magnetic ground state of an Fe ML on W and Ta (110) surfaces. A reorientation of the easy axis from in-plane to out-of-plane is found in the case of Fe/W (110) system.…”
Section: Introductionmentioning
confidence: 99%